Prevalence of Cholesteatoma in School Children of Nepal - Maharjan, Milan; Rajbhandari, Samira; Subba, Shristi; Gupta, Anjani (International Archives of Otorhinolaryngology, 2025)
Cholesteatoma remains a serious condition that poses a challenge to otolaryngologists around the world. It is found to be more aggressive in the pediatric group than in adults. If left untreated, the disease can be dangerous due to its ability to expand and destroy bones, leading to complications such as hearing loss, vestibular dysfunction, facial paralysis, and intracranial infections.To find out the prevalence of cholesteatoma in the school-aged children of Nepal.This is a retrospective study conducted within a span of 10 years from 2014 to 2024 in which all medical records of the school-based ear screening programs were studied. Data including personal details, brief history, and ear and audiometry findings were recorded. All suspected cases of cholesteatoma were reexamined under microscope at our institute, and only those with confirmed diagnosis of chronic otitis media (COM) with cholesteatoma were included in the study.Out of the total of 143,544 children screened, COM with cholesteatoma was diagnosed in 0.20% (n = 282), and COM in total in 7.56% (n = 10,853). Hearing loss was seen in 273 (96.81%) of the 282 cases, with conductive hearing loss being the most common type of hearing loss.There is a higher prevalence of cholesteatoma in Nepalese children. Early diagnosis with proper management helps reduce the chances of life-threatening complications. Thus, having regular screening programs in school children will help in reducing morbidity.
Keywords: cholesteatoma; prevalence; children; hearing loss; Nepal